Body weight and growths curve parameters evaluation of three chicken genotypes (Gallus gallus domesticus) reared in claustration - N’dri, Aya Lydie; Koua, Bekoin Hermann Wenceslas; Ahouchi, Valencourt Simon; Adepo-Gourene, Abouo Beatrice (Journal of Advanced Veterinary and Animal Research, 2018)
Objective: The current study was undertaken to evaluate intensively reared indigenous slow-growing normally feathered (I-nana), commercial heterozygous naked neck (C-Nana), and commercial normally feathered (C-nana) chicken for their body weight and growth curve parameters. Material and methods: A total of 132 birds were used in this study. Specifically, chickens flock consisting of 21 I-nana (8 males and 13 females), 20 C-Nana (8 males and 12 females) and 91 C-nana chickens (32 males and 59 females) were marked individually and reared together in a single room under uniform feeding, care and management. Body weight of individual hen and rooster of each genotype was measured weekly up to 12 weeks of age and then at 30 weeks of age. Parameters of growth curve were determined using Gompertz’s equation. Results: Commercial heterozygous naked neck and commercial normally feathered chickens exhibited significantly (P<0.01) higher daily weight gain (DWG) than indigenous normally feathered counterparts at the first two phases of growth during 12 weeks of age (the DWG1-3wk for C-Nana, C-nana and I-nana were 04.46±0.93 gm, 05.01±1.10 gm and 02.38±0.78 gm, respectively, and DWG3-12 wk for C-Nana, C-nana and I-nana were 16.60±3.70 gm, 16.23±3.4 gm and 08.01±1.74 gm, respectively). However, at the third phase of growth 12 through 30 weeks of age, the normally feathered indigenous chickens (I-nana) had a significantly (P<0.01) higher DWG12-30 wk (02.91±0.81 gm) when compared with C-nana (02.53±1.25 gm). The growth curves of chickens showed out distinctive inflexion points at 46.91d, 50.68d and 51.22d (P<0.01) for three different C-nana, C-Nana and I-nana genotypes, respectively. The maturation rate per day was low for indigenous normally feathered birds (0.0282 gm), medium for commercial heterozygous naked neck and high for commercial normally feathered (0.0304 gm) chickens. The asymptotic weights were 823.7 gm, 1594.2 gm and 1506.9 gm for normally feathered indigenous, commercial naked neck and normally feathered chickens, respectively (P<0.01). Initial specific growth rate of commercial normally feathered (0.1676 gm) and naked neck (0.1479 gm) chickens were higher than that of normally feathered indigenous counterparts (0.1196 gm). Conclusion: The findings of the study reveal that the growth of normally feathered indigenous genotype was lower than those of commercial naked neck and commercial normally feathered chickens. However, the indigenous feathered chickens showed higher growth rate during the last phase of growth compared with the commercial feathered chickens. The estimate of the curve parameters seems to be an important tool for the selection of slow-growing traditional chickens for improvement. http://doi.org/10.5455/javar.2018.e265